Multi-Actor Collaboration In Counter-Terrorism: A Bibliometric Study - Rachmad Safa’at; Abdul Hakim; Muhammad Nur Rafi’ S (Publisia: Jurnal Ilmu Administrasi Publik, 2025)
Scholars who have studied terrorism for many years have emphasized the importance of considering a multi-actor collaborative approach in studying and addressing it. Therefore, this study aims to evaluate international publication trends regarding multi-actor collaboration using the Scopus database through bibliometric analysis from 2009 to 2025. Data visualization and analysis were conducted using Scopus, Biblioshiny, and VOSviewer. The results show that counter-terrorism is widely discussed within the framework of multi-actor collaboration, focusing on planning and implementation. In addition, multi-actor collaboration in counter-terrorism appears to be promising through the theme of technological advancements and computer science. This result is expected to contribute to the novelty of future studies on multi-actor collaboration in counter-terrorism efforts.